ค่ารักษาพยาบาลในระบบโครงการเบิกจ่ายตรง (MEDICAL EXPENSE PROCEDURES OF DIRECT PAYMENT SYSTEM) - สุขศาลา, สุนิษา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ บทความนี้มีจุดมุ่งหมาย เพื่อเสริมสร้างความเข้าใจในเรื่องการเบิกจ่ายค่ารักษาพยาบาลในระบบจ่ายตรงแก่บุคลากรของรัฐและบุคคลทั่วไปที่เกี่ยวข้อง โดยได้รวบรวมข้อมูล รายละเอียดและสาระสำคัญของระบบจ่ายตรงค่ารักษาพยาบาลจากเอกสาร สื่ออิเล็กทรอนิกส์และหนังสือส่วนราชการ เพื่อเป็นประโยชน์แก่บุคลากรของรัฐและบุคคลทั่วไปที่เกี่ยวข้อง เพื่อจะได้นำไปเป็นแนวทางในการปฏิบัติให้ถูกต้องตามระเบียบและหลักเกณฑ์การเบิกจ่ายเงินค่ารักษาพยาบาลของส่วนราชการต่อไป Abstract The purpose of this article is to promote the understanding for medical expense procedures of the direct payment system to government officers and related people. By collecting data, details and main contexts of direct payment system from medical documents, electronic media and government documents, this is in order to give usefulness to government officers and related people following the guidance of correct government payment procedures.